Carbon dioxide (CO2) as an alternative contrast agent in percutaneous transluminal angioplasty procedures for chronic limb-threatening ischemia patients with chronic kidney disease - Vori, Ira; Kurnianingsih, Novi (Universitas Brawijaya, 2024)
Background: Chronic limb-threatening ischemia (CLTI) is a very morbid illness that significantly reduces quality of life. The severity of this disease may necessitate revascularization or amputation.Arteriography is frequently performed for the planning of revascularization. Patients with compromised kidney function need alternative contrast agents.CO2 may be utilized in lower extremity vascular diagnostics and intervention, especially in patients at risk for contrast-induced nephropathy (CIN).Case Illustration: An 80-year-old female with bilateral leg pain and leg swelling had an ulcer on her toe for 2 weeks. She had a history of intermittent claudication for 1 year, hypertension for 5 years, kidney stones for 2 years, and chronic kidney disease for 1 year. She underwent an ECG, laboratory, USG, DUS, and CT-angiography examination. From her laboratory result, her initial creatinine was 5.02 mg/dL (eGFR 8 mL/m/1.73 m2). After good hydration, it became 1.28 mg/dL (eGFR 39 mL/m/1.73 m2). After a CT-angiography procedure, her creatinine level was increased (3.7 mg/dL; eGFR 10.9 mL/m/1.73 m2). She was diagnosed with CLTI Rutherford V Fontain 3 left lower extremity. She suggested doing an angioplasty procedure with a safer contrast agent. An angioplasty procedure was done at RSSA Malang with CO2 contrast. After the procedure, her leg pain improved, and her creatinine didn’t elevate.Conclusion: CO2 angiography might be used as a safe alternative contrast medium in patients with CLTI, which benefits the preservation of renal function and prevents limb amputations.